2014
DOI: 10.1186/s12989-014-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative iron oxide nanoparticle cellular dosimetry and response in mice by the inhalation and liquid cell culture exposure routes

Abstract: BackgroundToxicity testing the rapidly growing number of nanomaterials requires large scale use of in vitro systems under the presumption that these systems are sufficiently predictive or descriptive of responses in in vivo systems for effective use in hazard ranking. We hypothesized that improved relationships between in vitro and in vivo models of experimental toxicology for nanomaterials would result from placing response data in vitro and in vivo on the same dose scale, the amount of material associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…One interesting question is the dose comparison. In a study on iron oxide NPs, Teeguarden and co-workers concluded that when considering target tissue dosimetry, especially with a focus on macrophages, a good conformity between target cell doses triggering inflammatory processes in vitro (8-35 pg/cell) and in vivo (1-100 pg/cell) was observed [32].…”
Section: Discussionmentioning
confidence: 99%
“…One interesting question is the dose comparison. In a study on iron oxide NPs, Teeguarden and co-workers concluded that when considering target tissue dosimetry, especially with a focus on macrophages, a good conformity between target cell doses triggering inflammatory processes in vitro (8-35 pg/cell) and in vivo (1-100 pg/cell) was observed [32].…”
Section: Discussionmentioning
confidence: 99%
“…Models and methodologies for particle dosimetry that enables the determination of the dosage delivered to cells have already been presented, and it has been shown that usage of the cellular dose rather than administered dose improves the correlation between dose and response to particles in vitro and in vivo. [48][49][50][51] In addition to the impact of SPION-intrinsic properties, we found some strongly pronounced cell type-dependent differences affecting cellular SPION uptake. In our studies, we used 4 different breast cancer cell lines that strongly differ from each other concerning the expression of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (Her2/ERBB2) and a cellular proliferation marker Ki-67.…”
mentioning
confidence: 86%
“…Cellular uptake of ENMs can be monitored using particles bearing various detectable and quantifiable markers. Examples include fluorescently labeled polystyrene beads [61,62], superparamagnetic iron oxide tracer particles [61,63], and neutron activated tracer particles [60]. Alternatively, uptake can be measured by direct quantification of the ENM material using inductively coupled plasma mass spectrometry (ICP-MS) [64][65][66].…”
Section: Integrated In Vitro Dosimetry Platformsmentioning
confidence: 99%